Optimization of jet fuel autothermal reformer for fuel cell applications - Azman, Nur Aifaa (2006)
Fuel cell is an electrochemical device that converts hydrogen and oxygen into electricity without combustion. In this research jet fuel is converted to hydrogen for fuel cell application via autothermal reforming process. The autothermal reforming process consist of three different processes which are total oxidation (TOX) and partial oxidation (POX) processes, steam reforming (SR) process, water-gas shift (WGS) process and preferential oxidation (PROX) process. Jet fuel, air or oxygen and water was fed first to the conversion reactor for the reforming process then to the equilibrium reactor for the water-gas shift process to occur. Finally, to the conversion reactor where the preferential oxidation process takes place. The base case simulation model of the hydrogen production plant was developed based on the understanding of the process. The steady-state simulation was developed using Aspen HYSYS 2004.1. Optimization of the plant was carried out phase by phase to get the optimum value of water and air should be fed into the ATR reactor at 100 kgmole/h of jet fuel. The optimum ratios for air-to-fuel (A/F) and steam-to-fuel (S/F) are 35 and 18 respectively, to produce 39.4% of hydrogen and less than 10 ppm of CO with 80.4% of fuel processor efficiency.